Trees and Livelihoods in Karamoja, Uganda - Egeru, Anthony; Okia, Clement; Leeuw, Jan de (ResearchGate, 2014)
This report presents results of a rapid desk review of academic and grey literature on the evidence relating to trees and livelihoods in Karamoja a region in north eastern Uganda. The review identified the range of problems in the Karamoja sub-region; benefits of trees to people and communities living in Karamoja; the role of trees in resilience building; role of trees in agricultural production, traditional knowledge of trees in Karamoja; threats to trees, drivers of development in Karamoja; tree-based initiatives in the sub-region; and opportunities for action research in Karamoja. Using their experiences in the Karamoja subregion and other similar ecosystems in Africa, the authors provide insights of the contribution of trees to livelihoods in Karamoja. Karamoja sub-region is a semi-humid to semi-arid sub-region in north eastern Uganda covering approximately 27,200 km2. It has a complex range of problems including: historical injustices, misconceptions of the sub-region and its people, poor infrastructure climate variability and change, existence of several agricultural risks, weather based vagaries, low agricultural productivity, a declining pastoral production system, increasing environmental degradation orchestrated by a number of mal-adaptations, and poor performance of the region with respect to development indicators as compared to other parts of Uganda. The climate in Karamoja sub-region is generally harsh with high rainfall variability and high evapotranspiration. The sub-region’s rainfall regime ranges between 350-1000 mm per annum. This precipitation is usually sporadic and falls in one rainy season. The sub-region generally suffers from poor rainfall distribution rather than from low rainfall totals. However, it is the intensity and the variability, particularly the existence of sporadic intense wet periods followed by drought events that has always had debilitating impacts on the sub-region. There is wide evidence to suggest that trees provide a range of services and benefits to the people and communities living in Karamoja. Following the Millennium Ecosystem Assessment (http://www.millenniumassessment.org) analysis, these are categorised into four sub-groups: provisioning, regulating, supporting and cultural services. This review reveals that the Karamojong1 derive a wide number of herbs and medicinal products for humans and livestock from trees. Consequently, the Karamojong have high levels of ethnopharmacological and enthanoveterinary knowledge. Firewood, charcoal, building materials, gums, resins and extractives are also harvested from different tree species within the sub-region. Further, trees provide forage and browse to livestock during both dry and rainy seasons. Browse is particularly important during the dry seasons when acacia pods are utilised. The trees in the sub-region act as wind breaks against the strong winds that emerge from the Turkana plains in Kenya; trees also help to control soil and water erosion. In places where trees have been cleared, soil erosion is strongly evident, developing into gullies.
Keywords: Trees; Livelihoods; Uganda